Feasibility of determination of low-head hydroelectric power development at existing sites: North Hartland Dam Project. Feasibility report (Vermont Electric Cooperative, Inc., Johnson (USA), 1979)
The feasibility of constructing a low-head hydroelectric power plant at the North Hartland Dam in Vermont was investigated. Evaluation of technical, economic, environmental, safety, and regulatory aspects led to the conclusion that the North Hartland Dam Hydroelectric Project is a technically feasible concept. The proposed project will have a recommended 6000 kW nominally rated capacity at a 52 ft turbine design head and 1680 cfs demand flow. The gross generation expected from the project is 11,980,000 kWh per year. It is estimated that the project will cost $8,997,000 at 1978 price levels, with no allowance for funds during construction. The project will provide peaking power at a levelized cost of about 41 mills per kWh at 1979 price levels, based on 7% cost of money, a 1985 commissioning date, and allowing for funds during construction and cost escalation over a 30 y period. The benefit-cost ratio compared with an equivalent oil-based generation source over a similar period is estimated as 1.06. (LCL)